2010
DOI: 10.1007/s12564-010-9133-x
|View full text |Cite
|
Sign up to set email alerts
|

How do Turkish nursing students plan their career after the graduation?: a questionnaire survey

Abstract: This research was planned as a cross-sectional and descriptive study for the purpose of determining nursing students' expectations from a workplace and what department, area, and positions they want to work in after graduation. The research population was comprised of the four university-based schools of nursing in Ankara province. The sample was comprised of 447 nursing students. A questionnaire developed by the researchers in light of information in the literature was used for data collection and had three s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 16 publications
(24 reference statements)
0
15
0
1
Order By: Relevance
“…Generally, students like to be in academic part (education) or management position after graduation. [ 1 23 ] Students in this study also mentioned that it does not matter they work in public or private sectors. Thus, for this reason, the students who would like to be bedside nurses to responsible for direct nursing care can help dealing with nursing shortage in Indonesia, and it may prevent them from developing wrong expectations and goals in their career planning.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…Generally, students like to be in academic part (education) or management position after graduation. [ 1 23 ] Students in this study also mentioned that it does not matter they work in public or private sectors. Thus, for this reason, the students who would like to be bedside nurses to responsible for direct nursing care can help dealing with nursing shortage in Indonesia, and it may prevent them from developing wrong expectations and goals in their career planning.…”
Section: Discussionmentioning
confidence: 84%
“…However, this result is not in line with Yildirim's study found that more than half of the nursing student are not including direct patient care in their career planning. [ 1 ] Followed by Rognstad et al . determined that nursing students were less interested in giving care and help to others.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations